2012
DOI: 10.5424/sjar/2012101-134-11
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and digestibility of some browse plant species collected from Algerian arid rangelands

Abstract: Many wild browse and bush species are undervalued mainly because of insufficient knowledge about their potential feeding value. The objective was to evaluate some nutritional attributes of various Algerian browse and shub species (Atriplex halimus, Artemisia campestris, Artemisia herba-alba, Astragalus gombiformis, Calobota saharae, Retama raetam, Stipagrostis pungens, Lygeum spartum and Stipa tenacissima). Chemical composition, phenols and tannins concentration, in vitro digestibility, in vitro gas production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
5
33
0
1
Order By: Relevance
“…The CP contents of DPBP found in the present work for waste dates were in agreement with those reported by Longuo et al (1989), Chehma and Longuo (2004) and Genin et al (2004) who reported a low nitrogen content (4.5%) for waste dates of deglet noor variety. The CP content of DPBP was thus below the level required (70-80 g CP/kg DM) for optimum rumen function (Van Soest, 1994;Boufennara et al, 2012). Norton et al (1994) concluded that such a low dietary N supply is not sufficient to ensure an optimal metabolic activity and growth of ruminal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The CP contents of DPBP found in the present work for waste dates were in agreement with those reported by Longuo et al (1989), Chehma and Longuo (2004) and Genin et al (2004) who reported a low nitrogen content (4.5%) for waste dates of deglet noor variety. The CP content of DPBP was thus below the level required (70-80 g CP/kg DM) for optimum rumen function (Van Soest, 1994;Boufennara et al, 2012). Norton et al (1994) concluded that such a low dietary N supply is not sufficient to ensure an optimal metabolic activity and growth of ruminal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the importance of tree foliage for ruminant nutrition has led to several studies aimed at evaluating leaf forage productivity, chemical composition and digestibility (e.g. Boufennara et al 2012). Proximate and fatty acid (FA) composition, phenolic concentration and digestibility have been largely assessed for various fodder tree species in several environments such as savanna (Tefera et al 2008), tropics (Arigbede et al 2012), subtropics (Prakash et al 2009), American temperate region (Ricklefs and Matthew 1982), Mediterranean region (Kökten et al 2012) and non-European alpine areas (Khanal and Subba 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Among them there are influence of heat stress on protein quality and breeding drought tolerant varieties of plants (Thomas, 2015), efficient use of cultures under dryland conditions (Robles et al, 2008;Boufennara et al, 2012), increasing the bioavailability of minerals from grain crops (Gupta et al, 2015). More efficient use of perennial crops that require less protection chemicals and Asian J.…”
Section: Introductionmentioning
confidence: 99%